Principal Leadership Strategy in Improving the Performance of Muhammadiyah Elementary School Teachers - Nita Listiyani; Suyatno Suyatno; Achadi Budi Santosa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Teacher performance is a crucial factor in achieving effective educational management. One of the principal's primary roles is to build teacher performance through appropriate leadership strategies. This study aims to analyze the principal's leadership strategies in improving teacher performance at Muhammadiyah Elementary School in the Colombo Complex. The study employed a qualitative case study approach, with data collection techniques including in-depth interviews, observations, and documentation. Research informants included the principal, vice principal, and teachers. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the principal's leadership strategy in improving teacher performance is carried out through humanistic-based transformational leadership that prioritizes role models, empathetic communication, and teacher empowerment. This strategy is realized through measurable instructional development planning, professional training, and strengthening teacher learning communities. In addition, the principal provides collaborative and reflective academic supervision to provide constructive feedback to teachers. These efforts are supported by strengthening organizational culture and internal discipline built on a foundation of togetherness. Overall, this leadership strategy has proven effective in improving teacher professionalism and creating a positive and sustainable school work culture.